Current Understanding of Epigenetics Driven Therapeutic Strategies in Colorectal Cancer Management - Deka, Dikshita; Scarpa, Marco; Das, Alakesh; Pathak, Surajit; Banerjee, Antara (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2021)
Colorectal cancer is known to be the paramount reason for cancer deaths around the globe. It occurs due to the aggregation of epigenetic and genetic alterations in colon epithelial cells that transmute them into adenocarcinomas. Epigenetic mechanisms are interpreted as the changes in expression of the gene which is not associated with the alterations in the principal DNA sequence, while genetic changes involve modifications in oncogenes and tumor suppressor genes. The changes in the epigenetic in colon cancer that transmute colonic epithelial cells include chromatin modifications, microRNA expression, telomere length, and DNA methylation. DNA hypermethylation causes down-regulation and unsuitable expression of specific microRNA which can behave like tumor suppressor genes. Histone modifications can also influence the chromatin remodeling and gene expression, hence performs an eminent function in the silencing of the gene in colon cancer. Moreover, the telomere/telomerase interaction is a prime mechanism to embrace both cellular replicative potential and genomic instability and its malfunction plays a primary role in colon cancer. Deducing the genesis and the function of epigenetic abnormality in colon cancer pathogenesis will lead to potent prevention and therapeutic approach for colon cancer patients. Epigenetic drugs which emphasize the convertible essence of the epigenetic occurrences have accompanied the probability of epigenetic approach as a treatment alternative in colon cancer. Hence, this review is undertaken to critically envelop the recently advanced events in colorectal cancer therapies with a special emphasis on remedies targeting epigenetic modulators and future challenges towards therapeutic interventions.
Keywords: chromatin remodeling